2016
DOI: 10.1073/pnas.1615671113
|View full text |Cite
|
Sign up to set email alerts
|

Serum stimulation of CCR7 chemotaxis due to coagulation factor XIIa-dependent production of high-molecular-weight kininogen domain 5

Abstract: Chemokines and their receptors play a critical role in immune function by directing cell-specific movement. C-C chemokine receptor 7 (CCR7) facilitates entry of T cells into lymph nodes. CCR7-dependent chemotaxis requires either of the cognate ligands C-C chemokine ligand 19 (CCL19) or CCL21. Although CCR7-dependent chemotaxis can be augmented through receptor up-regulation or by increased chemokine concentrations, we found that chemotaxis is also markedly enhanced by serum in vitro. Upon purification, the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Researchers have found that CCR7 is highly expressed on human B cells, expanded T cells instead of naïve T cells (38) and dendritic cells (39) and its expression on peripheral T cells was positively related to the chemotactic migration of T cells to CCL19 and CCL21 (40). On the other hand, CCR7 mediated chemotaxis required the existence of CCL19 or CCL21 (41). In vitro experiment indicated that recombinant CCL19 showed potent chemotactic activity for T-cells and Bcells but not for granulocytes and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that CCR7 is highly expressed on human B cells, expanded T cells instead of naïve T cells (38) and dendritic cells (39) and its expression on peripheral T cells was positively related to the chemotactic migration of T cells to CCL19 and CCL21 (40). On the other hand, CCR7 mediated chemotaxis required the existence of CCL19 or CCL21 (41). In vitro experiment indicated that recombinant CCL19 showed potent chemotactic activity for T-cells and Bcells but not for granulocytes and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, the target can then be identified through MS analysis. Although this elegant ligand-based receptor-capture (LRC) strategy has resulted in successful identification of certain membrane receptors (Li et al, 2016, 2018; Ponda and Breslow, 2016), identification can only occur for receptors carrying an N-linked glycan in close proximity to the ligand-binding site. To overcome this glycan dependency, others have recently developed ligand-derived probes harboring photoaffinity labels to capture target receptors (Blex et al, 2017; Thomas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we established an in vitro method for measuring the effect of perioperative factors on the adhesion ability of the LS174T colon cancer cell line using serum from patients undergoing colon cancer surgery. Commonly used methods for cell adhesion assays typically include staining attached cells and using fluorescence for endpoint measurements [39][40][41], but by using the method developed in this paper, it is possible to monitor real-time cell adhesion for the entire adhesion period. While this method does not allow us to distinguish between initial sedimentation, cell attachment, cell spreading and stable cell adhesion, the mentioned are all part of the passive cell adhesion process [42].…”
Section: Discussionmentioning
confidence: 99%